Reduction of the domains of basic elementary functions to arbitrary small intervals - Shishkov, Dimitar (Ann. Sofia Univ. Fac. Math. and Inf., 1995)
Algorithms for reduction of the initially constraint unlimited domains of basic elementary functions of the system {e^x, x, g x, x, x, x} to sufficiently small intervals are treated.